Marketing Risk Management and Mapping Based on Geographic Information System in The Micro, Small, and Medium Enterprise in Tasikmalaya City - Syti Sarah Maesaroh; Ardli Swardana; Asep Nuryadin; Oding Herdiana; Risma Rahatuningtyas (Jurnal Ilmiah Manajemen dan Bisnis, 2022)
The current COVID-19 pandemic has greatly impacted the economic sector, especially Micro, Small, and Medium Enterprises (MSMEs). Restrictions on physical mobility hinder the marketing of MSMEs’ products, which is usually carried out directly. This is one of the important risks to be studied in depth. The purpose of this study is to determine the management system and mapping of marketing risks in MSMEs in Tasikmalaya City. The research method used in this study was descriptive quantitative. Data were collected through a closed questionnaire that was given to MSMEs. The obtained data were processed through a risk management system approach and then mapped using a Geographical Information System (GIS). The results showed that the highest marketing risks for MSMEs in Tasikmalaya City are increasingly fierce business competition, nonoptimal internet usage, and limited marketing coverage. Geographically, the level of marketing risks of MSMEs in Tasikmalaya City is in the medium category. Geographical marketing risk mapping can determine the most appropriate recommendations to deal with various risks faced according to regional characteristics.